The Role of the Mosque Kenaziran Agency in Improving the Ability to Read the Qur'an for Worshippers at Amar Ma'ruf Mosque - Muhammad Riza Arifin S (LP. Ma'arif Janggan Magetan, 2024)
Reading the Koran is an obligation for every Muslim. However, in order to improve the ability to read the Qur'an for the congregation, motivation and mentors are needed to achieve the expected goals. This writing aims to describe the role of the Mosque Religious Agency in improving the ability to read the Al-Qur'an for the congregation at the Amar Ma'ruf Mosque which is located on Jl. Gurilla, Sidorame Team, District. Medan Struggle, Medan City. This research uses descriptive qualitative research. The data collection techniques are observation, interviews and documentation analysis. After conducting research, the results were obtained that there is a role for the Mosque Trust Board which has made the mosque prosperous by holding coaching activities to improve the ability to read the Al-Qur'an for the congregation. However, on the other hand, there are several inhibiting factors in increasing the ability to read the Al-Qur'an for the congregation, namely the congregation's lack of awareness of the importance of reading the Al-Qur'an, lack of motivation and guidance and lack of time allocation. The supporting factors include supporting facilities, organized activities, appropriate methods and the presence of active mosque youth.